Religious Attendance, Religious Importance, and the Pathways to Depressive Symptoms in Men and Women Aged 50 and Over Living in Ireland - Mc Garrigle, Christine; Kenny, Rose; Tobin, Katy (My University, 2019)
Objectives: We aimed to explore the relationship between religiosity and depressive symptoms longitudinally. Method: We used four waves (2009-2016) of the Irish Longitudinal Study on Ageing (TILDA) to create growth curve models (GCM) of depressive symptoms and religious attendance/importance in a sample aged 50+ in Ireland and structural models to assess the longitudinal associations between religious attendance/importance and depressive symptoms. We tested whether this relationship was mediated by social connectedness. Results: GCM showed that higher religious attendance at baseline was associated with lower baseline depressive symptoms, while higher religious importance was associated with higher baseline depressive symptoms. Social connectedness partially mediated the baseline associations between religious attendance and lower depressive symptoms. There were no associations between religious factors and the development of depressive symptoms over time. Discussion: This study found that the relationship between religion and depressive symptoms is complex, and any protective effect was driven by religious attend
PUBLISHED
Keywords: depression, religion/spirituality, social networks; Ageing